Study and Performance Analysis of Dedicated In-Band Control Channels for Cognitive Radio Networks - Tamilarasan, S; Kumar, P (International Journal of Computer Sciences and Engineering, 2025)
Recently wireless ad hoc network is an emerging new technology. Due to its emerging capability it faces spectrum scarcity problem. Resources and channels in CRN (cognitive radio network) would be allocated based on dynamic access methods with respected to sensed radio environment. Cognitive Radio (CR) technology provides a smart and optimistic solution to the problem of spectrum scarcity through Dynamic Spectrum Allocation (DSA). Due to the nature of Cognitive Radio Networks (CRNs), where two networks area unit active at the same time, a signiﬁcant quantity of control messaging is essential in order to coordinate channel access, schedule sensing, and establish release connections. Efﬁcient Control Plane messaging can be achieved by the selection of a suitable Control Channel (CC). This paper provides a comparative study of probable systems for providing reliable channels dedicated to the coordination and information distribution in License-Exempt (LE) bands. This involves determining the potential and limitations of every method.